Landscapes of the Jihad - Deviji, Faisal (New Dehli, 2005)
The militant Islam represented by Al Qaeda is often described as a global movement. Apart from the geographical range of its operations and support, little else is held to define it as 'global'. Its militants' international mobility and their technological sophistication are portrayed as the only signs of the jihadis' globalisation. Landscapes of the Jihad explores the features that Al Qaeda and other strands of militant Islam share in common with global movements such as environmentalists and anti-globalisation protesters. These include a decentralised organisation and an emphasis on ethical rather than properly political action. Devji brings these and other characteristics of Al Qaeda together in an analysis of the jihad that locates it squarely within the transformation of political thought after the Cold War. The jihad emerges from the breakdown of traditional as well as modern forms of authority in the Muslim world. It is neither dogmatic in an old-fashioned way nor ideological in the modern sense, and concerned neither with correct doctrinal practice in the present nor with some revolutionary utopia of the future. Instead it is fragmented, dispersed and highly individualistic.
Keywords: "Terrorism-religious aspects, Islam, Globalization, Jihad"